A Look at How Tabletop Technology Influences Table Turn and Service Labor Usage in Table-Service Restaurants. (August 2019) - Susskind, Alex M.; Curry, Benjamin
Using a table-service casual dining restaurant chain, we used direct observations to examine how guests' use of tabletop technology affected their dining time and front of house labor usage. Results from our study showed that dining time was significantly reduced for guests who used the tabletop devices to either order, or order and pay for their meals by 17% and 31%, respectively. We also found that server contact time and table service time required by the servers to manage their guests' experiences was significantly decreased for the tables that used the tabletop devices compared with the tables that did not use the devices. Practical and managerial implications are discussed.